OTTOMAN CENSUS OF SMALL LIVESTOCK GROWN IN KADILUK SRE-BRENICA IN 1596. Year (Heritage, 2024)
In this paper was announceda list of villages that were engaged in the breeding of small livestock, in the area, that according to the Ottoman administrative division, was part of the kazâof Srebrenica in the Sanjak of Smederevo. The census was carried out in 1596 and included 44 villages of the mentionedkazâ, i. e. the territories of today's municipalities ofBajina Bašta and Ljubovija, i. e. Azbukovica. The determined number of small livestock totaled 38,272 heads. The census enables the calculation of total quantities of individual livestock products. In the observed area were kept the autochthonous Sjenica–Pešter sheep and the Balkan goat of the higher areas. Bearing in mind their production potential, and after the percentage representation of sheep and goats in the mentioned part ofkazâ of Srebrenicawas established, the approximate annual production of milk, wool and goat’s hair was estimated.Based on three models, the percentage of sheep and goats was determined. The first is based on the statistical data of the former Užice district – which mostly covered the observed part of the kazâ of Srebrenica– in 1900. The second calculation method is based on one piece of data from the Dubrovnik archives on imports, and the third model is constract on archaeozoological data from the site of Gradina – Erčege (14th–15th century), near Ivanjica (third column of the table).The number of sheep and goat skins produced annually would be approximately the same as the number of recorded heads, while the approximate number of small livestock was used for food or trade. It should be kept in mind that the obtained values ​​were calculated based on the number of livestock included in the census, while the real number of livestock in the observed area was probably higher.
Keywords: sheep tax (adet-i âgnâm), kazâ of Srebrenica, 16th century, Ottoman Empire, Sanjak of Smederevo, Bajina Bašta, Ljubovija